Suspicious minds: Can features of the local neighbourhood ease parents' fears about stranger danger?. (June 2015) - Foster, Sarah; Wood, Lisa; Francis, Jacinta; Knuiman, Matthew; Villanueva, Karen; Giles-Corti, Billie
Abstract: Declines in children's independent mobility are frequently attributed to parents' fears about stranger danger, yet there is limited understanding of the factors that might aggravate (or ease) these concerns. We examined the social and built environment correlates of parents': (1) fears about strangers harming their child; and (2) perceptions of the likelihood this would actually happen. We also tested whether associations differed by area socio-economic status (SES) as parents in low income neighbourhoods, typically with more crime, may hold greater fears for their children's safety. Results suggest that regardless of SES, neighbourhood features that encouraged pedestrians, whilst minimising vehicle traffic, were most conducive to parents perceiving a safer neighbourhood. The natural surveillance generated by a more walkable neighbourhood may help alleviate parents' fears about strangers. Highlights: Parents' fear of strangers is implicated in children's declining independent mobility. There is limited awareness of the factors that shape parents' fears about strangers. We examined the correlates of parents' fear of strangers and perceptions of risk. Built environments that encouraged 'eyes on the street' correlated with lower fear. More walkable neighbourhoods may help alleviate parents' fears about strangers.